LncRNA AW112010 Promotes Mitochondrial Biogenesis and Hair Cell Survival: Implications for Age-Related Hearing Loss. (27th October 2019) - Su, Zhongwu; Xiong, Hao; Pang, Jiaqi; Lin, Hanqing; Lai, Lan; Zhang, Huasong; Zhang, Weijian; Zheng, Yiqing
Abstract : Long noncoding RNA (lncRNA) disorder has been found in many kinds of age-associated diseases. However, the role of lncRNA in the development of age-related hearing loss (AHL) is still largely unknown. This study sought to uncover AHL-associated lncRNAs and the function. RNA-sequencing was conducted to profile lncRNA expression in the cochlea of an early-onset AHL mouse model. RT-qPCR assay was used to validate the expression pattern of lncRNAs. ATP assay, JC-1 assay, mitochondrial probe staining, CCK-8 assay, Western blot, and immunocytochemistry were performed to detect the effects of lncRNA AW112010 in HEI-OC1 cells and the mouse cochlea. We identified 88 significantly upregulated lncRNAs and 46 significantly downregulated lncRNAs in the cochlea of aged C57BL/6 mice. We focused on the significantly upregulated AW112010. Silencing of AW112010 decreased the ATP level, mitochondrial membrane potential, and cell viability and increased mitochondrial ROS generation under oxidative stress in HEI-OC1 cells. AW112010 overexpression promoted cell survival in HEI-OC1 cells. AW112010 knockdown reduced mitochondrial mass and impaired mitochondrial biogenesis in HEI-OC1 cells. Activation of mitochondrial biogenesis by resveratrol and STR1720 promoted cell survival. The mitochondrial biogenesis process was activated in the cochlea of aged mice. Moreover, AW112010 regulated AMPK signaling in HEI-OC1 cells. Transcription factor Arid5b elevated in the aged cochlea and induced AW112010 expression and mitochondrial biogenesis in HEI-OC1 cells. Taken together, lncRNAs are dysregulated with aging in the cochlea of C57BL/6 mice. The Arid5b/AW112010 signaling was induced in the aged mouse cochlea and positively modulated the mitochondrial biogenesis to maintain mitochondrial function.